A Novel TBK1 Variant (Lys694del) Presenting With Corticobasal Syndrome in a Family With FTD-ALS Spectrum Diseases: Case Report - Seibert, Kaitlin; Smith, Heather; Lapins, Allison; Pytel, Peter; Mastrianni, James A. (Frontiers in Neurology, 2022)
Several variants of the TANK-Binding Kinase 1 (TBK1) gene have been associated with frontotemporal dementia - amyotrophic lateral sclerosis (FTD-ALS) spectrum diseases. Corticobasal syndrome (CBS) is characterized by asymmetric limb rigidity, dystonia or myoclonus, in association with speech or limb apraxia, cortical sensory deficit, and/or alien limb. It can result from a variety of underlying pathologies and although typically sporadic, it has been occasionally associated with MAPT and GRN variants. We describe here the proband of a family with multiple occurrences of FTD-ALS spectrum disease who developed an isolated right-sided primary asymmetric akinetic-rigid syndrome and subsequent speech and cognitive dysfunction associated with contralateral anterior temporal lobe atrophy on MRI and corresponding hypometabolism by FDG-PET. Genetic testing revealed a novel Lys694del variant of the TBK1 gene and Type A TDP-43 pathology in a predominantly frontotemporal distribution contralateral to the affected side. To our knowledge this is the first report of CBS as the initial expression of a TBK1 variant. This case emphasizes the importance of considering TBK1 genetic screening in patients with CBS, as this may be an underrepresented population on the spectrum of genetic FTD-ALS.